Fundamentals of logistics management - Lambert, Douglas M.
Fundamentals of Logistics Management provides a unique opportunity to leverage high profile, quality authorship into a market segment that has had little prior access to it. This text approaches logistics from a marketing perspective, which is unique to its competitors. It also integrates the area of marketing, accounting, finance, and manufacturing within the text